Vernolepin regulates apoptosis and autophagy via microtubule formation in ovarian carcinoma cells - Tu, Ju-Hong; Lou, Wei-Hua; Huang, Rong; Zhao, Ai-Min (Bangladesh Journal of Pharmacology, 2015)
The study demonstrates the effect of vernolepin on proliferation and apoptosis in ovarian cancer cell lines. The inhibition of cell growth was significant at 30 ?M concentration after 48 hours in both OVCAR-3 and SK-OV3 cell lines. Phase-contrast microscopic examination revealed a decrease in number of vernolepin-treated cells. A number of membranous structures and vacuoles were visible in the cytoplasm after 24 hours. After 48 hours chromatin condensation and nuclear fragmentation indicating typical apoptotic changes were observed. Vernolepin treatment lead to 83.6% cell viability compared to control. However the cell viability was increased to 93.7% on after starvation followed by vernolepin treatment. On the other hand, 3-MA in combination with vernolepin decreased cell viability to 54.5%. Annexin V-FITC/PI staining and FACS demonstrated that in OVCAR-3 and SK-OV3 cells treatment with vernolepin (30 µ?) for 48 hours caused apoptosis in 34.2% and 28.5% cells respectively. Thus, vernolepin-treatment in ovarian carcinoma cells leads to autophagy before the onset of apoptosis and protects cancer cells.